An Evaluation of the Research Chefs Association's Bachelor of Science in Culinology® Core Competencies. Issue 3 (2nd July 2016) - Cheng, Michael; Bosselman, Robert
ABSTRACT: Culinology® is the blending of culinary arts and food technology (RCA, 2010). As of 2016, there are 16 RCA-approved Culinology® degree programs, but there has been no research conducted on the effectiveness of the Culinology® competencies in preparing graduates for employment in the food product development industry. The purpose of this study was to determine whether the Culinology® core competencies prepared graduates for successful employment in the food industry. A sequential explanatory design was used for this research. In the first stage, a survey was used to measure the graduates' and employers' perceptions of the importance and frequency of use for each competency. In the second stage, interviews with selected graduates and employers were conducted to gain more insight on the results of the first stage. The results indicated that a gap existed between what the employers and graduates perceived as the most important competency, and graduates are not fully prepared for employment in the food product development industry.